Predictive Psychosocial Factors of Child-to-Parent Violence in a Sample of Mexican Adolescents - Suárez-Relinque, Cristian; del Moral Arroyo, Gonzalo; Jiménez, Teresa I.; Calleja, Juan Evaristo; Sánchez, Juan Carlos (Frontiers in Psychology, 2020)
The aim of this study was to carry out a psychosocial analysis of child-to-parent violence (CPV) in a sample of school adolescents, considering a set of individual variables (psychological distress, problematic use of social networking sites and perceived non-conformist social reputation), family variables (family communication) and sociodemographic variables (sex). The sample consisted of 3,731 adolescents (54% boys), aged between 14 and 16 years (M = 14.6 years, SD = 0.567), from the state of Nuevo León, Mexico. A stepwise regression analysis was applied. The results confirmed that the main predictors of CPV were perceived non-conformist social reputation, psychological distress, problematic use of social networking sites and problematic communication with parents. These results are interesting and have important implications for the prevention of CPV, since they provide information regarding a set of variables that have been analyzed mainly in the sphere of violence between peers, but not in the case of violence exerted by children towards parents.